Análisis regional y mundial del ranking científico de Scopus y Web of Science en la contabilidad y auditoría. - Arias Avila, Elizabeth Veronica (My University, 2021)
This document entitled Regional and world analysis of the scientific ranking of SCOPUS and Web Of Science in Accounting and Auditing corresponds to the development of the written dimension of the complex examination, said issue arises after observing that the national and regional scientific production presents deficiencies and does not have impact worldwide, also because students and academics lack sufficient skills, abilities and knowledge to locate the information that is considered most relevant. For the development of this research, the problem was identified: How does the identification of journals with the greatest scientific impact affect the production of research in Accounting and Auditing? For this purpose, the objective was to identify the journals that lead the Scopus and WOS rankings through the SCImago application for the improvement of bibliographic references in the production of research in Accounting and Auditing. The results show that in Ecuador and Latin America the publications in this area are poor and through the analysis of the indicators of scientific impact it was known that all the five journals that lead the ranking are European, specifically from England and the Netherlands, and that in the field regional Brazil is the main exponent. The present study concludes with the identification of the five main journals on Accounting and Auditing at the world level, the four best at the regional level and finally that the SCImago tool is very useful for the search for information and adds quality to the production of articles scientists.
El presente documento titulado Análisis regional y mundial del ranking científico de SCOPUS y Web Of Science en la Contabilidad y Auditoría corresponde al desarrollo de la dimensión escrita del examen complexivo, dicho tema surge tras observarse que la producción científica nacional y regional presenta deficiencias y no tiene impacto a nivel mundial, además porque las estudiantes y académicos carecen de las suficientes habilidades, destrezas y conocimiento para ubicar la información que se considera más relevante. Para el desarrollo de la presente investigación se identificó la problemática ¿Cómo la identificación de las revistas con mayor impacto científico incide en la producción de investigaciones en Contabilidad y Auditoría? Para ello se planteó como objetivo identificar las revistas que lideran el ranking de Scopus y WOS mediante la aplicación SCImago para el mejoramiento de las referencias bibliográficas en la producción de investigaciones en Contabilidad y Auditoría. Los resultados demuestran que en Ecuador y Latinoamérica las publicaciones en esta área son pobres y a través del análisis de los indicadores de impacto científico se conoció que todas las cinco revistas que lideran el ranking son europeas, de Inglaterra y Holanda específicamente, y que en el ámbito regional Brasil es el principal exponente. El presente estudio concluye con la identificación de las cinco principales revistas sobre Contabilidad y Auditoría a nivel mundial, las cuatro mejores a nivel regional y por último que la herramienta SCImago es de gran utilidad para la búsqueda de información y agrega calidad a la producción de artículos científicos.
Keywords: RANKING CIENTÍFICO; SCOPUS